PENGGUNAAN PENDEKATAN LINGKUNGAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DI SEKOLAH DASAR - Sefzirikayeni, Sefzirikayeni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Based on the research conducted, the data obtained from the first cycle results RPP 74.5 93.5 whereas in the second cycle, the assessment of the activities of teachers in the first cycle was 81, while in the second cycle 94, the results of assessment of student activity in the first cycle was 74.5, while in the second cycle 93.5, in the first cycle of learning outcomes 69 while on the second cycle of 80. It can be concluded on the use of action research approach can improve the learning environment in the fourth grade social studies Elementary School 15 Parit Panjang Lubuk Basung. Kata kunci: Hasil belajar, IPS, Pendekatan Lingkungan